PENGEMBANGAN KOMIK IPA BERBASIS KEARIFAN LOKAL TERINTEGRASI HOTS KELAS V MATERI ORGAN GERAK PADA HEWAN DAN MANUSIA - Gilang Setia Mahendra; Sugeng Eko Putro Widoyoko; Nur Ngazizah (LPPM Universitas Cipta Mandiri, 2024)
Teaching materials generally consist of knowledge, skills and actions that must be carried out by students in order to achieve the expected competencies. Comics are an example of teaching material. The current generation is less interested in preserving its local wisdom. Research Objectives: 1) Produce a science comic product based on integrated local wisdom HOTS class V Material on Movement Organs in Animals and Humans. 2) Knowing the feasibility of Class V HOTS Local Wisdom Based Science comics on Animal and Human Movement Organs. The method used in this research is R&D and uses the 4D (Four D) model, namely Define, Design, Develop and Disseminate. The results of this development research 1) Have produced a product in the form of